Features of the formation of independent Kazakhstan at the beginning of the XXI century - Kabayeva, Ж.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
Kazakhstan is a socially oriented state, which had clear vectors of the strategic direction of its development - first to get into the top 50, and then into the top 30 developed countries of the world. The purpose of the article is to show that the development of the country in this direction has made it possible to achieve certain significant results in the economic, political, and social spheres among the CIS countries. At the same time, there was an accumulation of negative things in the form of unresolved or postponed problems, which led to the strong social confrontation. This topic is relevant not only for understanding the formation of Qazaqstan Kazakhstan but also for understanding the socio-economic processes taking place in other developing countries; they all have both common and special properties. The methodology was based on comparative, synergistic, system-structural, and statistical methods. Based on the analysis, the article shows the specific achievements of the Republic of Qazaqstan in various fields using a comparative quantitative analysis. In this article, the dynamics of the development of the social sphere are shown on the basis of the use of accurate static data. These achievements were significant against the background of other developing countries, but they turned out to be far from being sufficient for the stable and sustainable development of an open Qazaqstan society. It is concluded that the strategic direction of the country’s development, with an emphasis first on the economy, and only then on other areas, was important and fruitful in the early years of the country’s formation. Qazaqstan is entering a new round of development, which means that accents are changing, new priorities are emerging. The time has come to resolve the accumulated economic and social problems; the time has come for reforms in all spheres, especially in the political sphere. The existing strong state power, by its decisive actions, will significantly accelerate the process of improving the socio-economic situation in the country. And here a breakthrough is possible. The significance of the article is determined by the possibility of applying the main findings in critically evaluating the achievements of the country, in order to understand its place among the developing countries of the world.